Analisis kecepatan dan fleksibilitas pergelangan tangan terhadap controlling dribbling test bolabasket KU 10 tahun - Rizky Kurniawan; Raymond Ivano Avandi (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
Background: Basketball is a team sport that requires mastery of fundamental techniques, one of which is the ability to control dribbling. At the early training stage, this skill often has not yet developed optimally. This study is motivated by the assumption that physical factors, particularly wrist speed and flexibility, play an important role in the dribbling quality of young basketball players. The purpose of this research is to analyze the influence of wrist speed and flexibility, both partially and simultaneously, on the ability to control dribbling among U-10 CLS West Surabaya basketball players.Research Objectives : This Study aims to examine the effect of speed and wrist flexibility on controlling dribbling ability in the U-10 basketball team of CLS West Surabaya. Methods : This study employed an associative-correlational design with a quantitative approach. The research subjects consisted of 22 athletes from the U-10 CLS West Surabaya team. Speed was measured using a 30-meter sprint test, wrist flexibility was measured with a goniometer, and dribbling control ability was assessed using the AAHPERD Basketball Control Dribbling Test. Data were analyzed using descriptive statistics, normality test, linearity test, partial correlation test, and multiple linear regression with IBM SPSS 26. Results : The findings indicate that, partially, wrist speed, flexors, and extensors do not have a significant effect on dribbling control ability, whether using the right or left hand. Simultaneously, these three variables also did not show a significant influence, with contributions ranging from 9.7% to 17.7%. Conclusion: The study concludes that the dribbling control ability of young basketball players is more strongly influenced by fundamental techniques, visuo-motor coordination, and playing experience. It is recommended that training programs place greater emphasis on the development of technique, coordination, and game-based practice.